Effect of Apple, Chestnut, and Acorn Flours on the Technological and Sensory Properties of Wheat Bread - Fryderyk Sikora; Ireneusz Ochmian; Magdalena Sobolewska; Robert Iwański (Applied Sciences)
The increasing interest in fibre-enriched and functional bakery products has led to the exploration of novel plant-based ingredients with both technological functionality and consumer acceptance. This study evaluates the effects of incorporating flours derived from apple (Malus domestica cv. Oberländer Himbeerapfel), sweet chestnut (Castanea sativa), horse chestnut (Aesculus hippocastanum), and red, sessile, and pedunculate oak (Quercus rubra, Q. petraea, and Q. robur) into wheat bread at 5%, 10%, and 15% substitution levels. The impact on crumb structure, crust colour, textural parameters (hardness, adhesiveness, springiness), and sensory attributes was assessed. The inclusion of apple and sweet chestnut flours resulted in a softer crumb, lower adhesiveness, and higher sensory scores related to flavour, aroma, and crust appearance. In contrast, higher levels of oak- and horse-chestnut-derived flours increased crumb hardness and reduced overall acceptability due to bitterness or excessive density. Apple flour preserved crumb brightness and contributed to warm tones, while oak flours caused more intense crust darkening. These findings suggest that selected non-traditional flours, especially apple and sweet chestnut, can enhance the sensory and physical properties of wheat bread, supporting the development of fibre-rich, clean-label formulations aligned with consumer trends in sustainable and functional baking.